Horticultural Reviews 2012
DOI: 10.1002/9781118351871.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Involved in Fruit Calcium Deficiency Disorders

Abstract: Understanding the mechanisms of calcium (Ca 2þ ) deficiency disorder development in plants has been a challenge for more than a 100 years. Previous studies support the hypothesis that Ca 2þ deficiency disorders can be triggered by mechanisms that reduce plant Ca 2þ uptake from the soil, fruit Ca 2þ uptake from the plant, and Ca 2þ translocation within the fruit, and also result in abnormal regulation of cellular Ca 2þ partitioning. Plant Ca 2þ uptake can be determined by Ca 2þ content and availability in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 169 publications
2
78
2
3
Order By: Relevance
“…A manutenção da umidade ideal do solo auxilia na absorção de cálcio pelas raízes (OLLE & BENDER, 2009). Como esse distúrbio está relacionado à deficiência de cálcio na planta, a manutenção da umidade do solo é importante tanto para permitir sua movimentação por fluxo de massa, quanto para possibilitar seu transporte via xilema até os frutos (FREITAS & MITCHAM, 2012). Contudo, a alta umidade do solo, devido às precipitações ocorridas no período de maior demanda de cálcio pelas plantas, provavelmente impediu a variação de umidade no solo entre os tratamentos com e sem cobertura plástica, justificando a ausência de resultados divergentes para essas características.…”
Section: Resultsunclassified
“…A manutenção da umidade ideal do solo auxilia na absorção de cálcio pelas raízes (OLLE & BENDER, 2009). Como esse distúrbio está relacionado à deficiência de cálcio na planta, a manutenção da umidade do solo é importante tanto para permitir sua movimentação por fluxo de massa, quanto para possibilitar seu transporte via xilema até os frutos (FREITAS & MITCHAM, 2012). Contudo, a alta umidade do solo, devido às precipitações ocorridas no período de maior demanda de cálcio pelas plantas, provavelmente impediu a variação de umidade no solo entre os tratamentos com e sem cobertura plástica, justificando a ausência de resultados divergentes para essas características.…”
Section: Resultsunclassified
“…Freitas & Mitcham (2012), based on a review of numerous studies of Ca deficiency factors, concluded that this phenomenon is the result of complex physiological processes which lead towards a decrease of Ca concentration in plant tissues, particularly the cell. Furthermore, the key role in the formation of bitter pit could have the translocation of Ca from the peduncle to the calyx part of the fruit.…”
Section: Introductionmentioning
confidence: 99%
“…The movement of calcium in the plant takes places mainly in the xylem, together with water. Therefore uptake of calcium is directly related to the transpiration rate of the plant, so conditions of high humidity, cold and a low transpiration rates may result in calcium deficiency [6]. The amaranth seeds were collected during the rainy season where humidity levels were high, so the calcium content may have been affected.…”
Section: Minerals: Calcium and Phosphorusmentioning
confidence: 99%
“…One other factor that may have affected the calcium levels is the soil pH. Usually soils that have a lower pH level contain less available calcium [6].…”
Section: Minerals: Calcium and Phosphorusmentioning
confidence: 99%